Studi Alternatif Perencanaan Bangunan Pelimpah Bendungan Pamukkulu dengan Tipe Mercu Bulat - Yoclina Edita; Melly Lukman; Erni Rante Bungin (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Spillway serves to overflow excess water to be discharged, so that the dam can be maintainedto the maximum extent. This Study aims to determine the flood discharge and to find out the alternative of the Pamukkulu Dam Spillway planning with the Mercu Bulat Type. Regional Average rainfall is calcuted by the Thiessen Polygon method. And analysed by calculating the design rainfall using the Gumbel method, Log Pearson Type III and Log Normal. Then determine the design flood discharge with a return period of 100 years using the HSS Gama Method 1. After calculating the design discharge,the Spillway planning is carried out with the Mercu Round Type. Based on calculations using the HSS Gama 1 method , the 100-yaer return period flood discharge is 219,099 m3/s and Spillway Building is a round crest with an energy height above the crest of 1,115 m.